6 - Corporate Social Responsibility and Workers’ Well-being in Nigerian Banks - Joseph A. Oluyemi; Muhammed A. Yinusa; Raji Abdulateef; Ibimidu Akindele (African Sociological Review, 2016)
The usual focus of Corporate Social Responsibility in Nigeria has always been on the society or the community where business is located while the place of workers as stakeholder in business is usually downplayed. This study examined the impact of corporate social responsibility on the wellbeing of workers in the Nigerian banking system. The objective was to know if adequate health facilities are provided for workers in the banks to meet their health needs when required. The study was conducted among ten commercial banks in Ilorin North-Central Nigeria while primary data was retrieved through self administered questionnaire from 160 participants. Participants were selected through a multi-stage sampling technique while the Statistical Package for Social Sciences (SPSS 19.0) was employed to analyse data retrieved from the field. Hypotheses formulated in the study were tested using the Chi-square statistical tool. Findings revealed that, 85.0% of the participants’ employers provided for them health facilities even though only 55.1% of the health facilities provided are adequate. A significant relationship was also found between participants’ wellbeing and health facilities provided p<0.05, while there was no significant relationship was between wellbeing of participants and adequacy of the health facilities provided by participants employers p>0.05. The study concluded that, even though some banks in the country provide health facilities for their workers, the health facilities provided are not adequate enough to meet the health needs of the workers. The study however, recommended a more comprehensive health plan for bankers that cover life saving health care services such as intensive care, surgeries and other life threatening diseases.